Commodity Price Shocks and Economic Growth Volatility: Evidence from Resource-Dependent Economies: JEL Classification: E32, F43, O13, Q02, C33 - Ahmad Firdaus Karim; Rizky Ananta Putra; Samuel T. Navarro (Mustard Journal De Ecobusin, 2026)
This study examines the effect of commodity price shocks on economic growth volatility in resource-dependent economies during the period 2026. The research aims to analyze how fluctuations in global commodity markets influence macroeconomic stability in countries highly dependent on natural resource exports. Using a quantitative panel-data approach, the study investigates 30 resource-dependent economies across Sub-Saharan Africa, the Middle East, Latin America, Southeast Asia, and Central Asia. The analysis employs Fixed Effects and Generalized Method of Moments estimations using macroeconomic data obtained from the World Bank, International Monetary Fund, and Worldwide Governance Indicators databases. The findings reveal that commodity price shocks significantly increase economic growth volatility, particularly in highly resource-dependent and oil-exporting economies. Resource dependence, inflation, and exchange rate instability intensify macroeconomic vulnerability, whereas institutional quality reduces the negative impact of external shocks. The study further demonstrates that countries with stronger governance systems and more diversified economic structures exhibit greater resilience during periods of commodity market instability. The findings provide important implications for economic diversification policies, fiscal stabilization strategies, and institutional reform in developing economies.